Verbal Communication in the Library Environment - Risti Nurul Azizah (IJAL (Indonesian Journal of Academic Librarianship), 2024)
A B S T R A C T This article explains the importance of communication between librarians as providers of information and users as recipients of information. Communication in the context of library organizations is an essential need in a variety of forms, including verbal communication, written communication, non-verbal communication, and direct face-to-face interaction. The focus of this article is related to effective verbal communication strategies in increasing interaction with library users. The research method uses case studies and literature studies, which he took from trusted sources or previous research. The purpose of this research was to provide informants with an overview of communication strategies in the library environment as well as steps that can be used as a reference to improve interaction between informants, librarians and libraries. Based on the results of research on verbal communication in the Muhammadiyyah University Ponorogo Library, one of which uses social media, namely You Tube, Instagram and Tik Tok, this was obtained based on observations that verbal communication in the Muhammadiyyah University library was solid, short and clear, this is in accordance with the theory that has been stated. convey the researchers before us.